Electrospun PLA/PCL fibers with tubular nanoclay: morphological and structural analysis - Haroosh, Hazim; Chaudhary, Deeptangshu; Dong, Yu (John Wiley and Sons Inc, 2012)
Biodegradable polymers are good candidates for a wide range of applications in tissue engineering and drug delivery because of their biocompatibility, their degradation, mechanical properties, and offer a sustained release of encapsulated drugs. The electrospun polymer nanofibrous materials can be used as carriers for hydrophobic and hydrophilic drugs. This research work focused on poly(lactic acid) (PLA) and blends of PLA with poly (ε-caprolactone) (PCL) that are reinforced with different concentrations of halloysite nanotubes (HNTs) and various cosolvents for electrospinning including chloroform : acetone, chloroform : methanol, and dichloromethane (DCM) : N,N, dimethylformamide (DFM). The fibers produced from the DCM : DMF system without HNTs were more uniform resulting in smaller fiber diameters as compared to the chloroform: methanol system due to the increased solution conductivity. The addition of HNT nanoparticles produced electrospun fibers with large diameters because the viscosity of the solution increased. Cosolvent was important in determining fiber diameters because it strongly influenced the solution viscosity and conductivity. HNTs had relatively small impact on the growth of a crystalline morphology in PCL–HNT composites. The solvent mixture of chloroform : methanol was better for PLA-based systems since PLA was found to have slightly higher crystallinity and larger enthalpy value indicating the improved structural orderness in the PLA polymer matrix